Why don't long-finned pilot whales have a widespread postreproductive lifespan? Insights from genetic data. (7th January 2020) - Nichols, Hazel J; Arbuckle, Kevin; Fullard, Karen; Amos, William
Abstract: In a handful of mammals, females show an extended postreproductive lifespan (PRLS), leading to questions over why they spend a substantial portion of their lifespan nonreproductive. Theoretical and empirical studies suggest that PRLS may evolve when 1) demographic patterns lead to increasing local relatedness as females age, and 2) females come into reproductive competition with their daughters, as these conditions lead to high relative benefits of helping kin versus reproducing in later life. However, evolutionary pathways to PRLS are poorly understood and empirical studies are scarce. Here, we use a dataset of 1522 individuals comprising 22 pods to investigate patterns of reproduction and relatedness in long-finned pilot whales Globicephala melas ; a toothed whale without species-wide PRLS. We find a similar relatedness structure to whales with PRLS: pods appear composed of related matrilines, and relatedness of females to their pod increases with age, suggesting that this species could benefit from late-life help. Furthermore, females with a large number of philopatric adult daughters are less likely to reproduce, implying intergenerational reproductive competition between females. This suggests that individuals may display a plastic cessation of reproduction, switching to investing in existing offspring when they come into competition with their daughters. To the best of our knowledge, this is the first time such a relationship has been described in relation to PRLS, and it raises questions about whether this represents a step towards evolving PRLS or is a stable alternative strategy to widespread postreproductive periods. Abstract : Not all long-finned pilot whales go through menopause despite having a social structure that predicts they may benefit from one. Humans and a few whales have a menopause, where females stop breeding part way through their lifespan, possibly to focus on helping their existing children and grandchildren. Despite being surrounded by relatives, long-finned pilot whales don't have widespread menopause. Instead, individual females with many offspring are less likely to breed, regardless of their age.